Pluteus aesontiensis (Agaricales, Pluteaceae) a new species in sect. Celluloderma - Dovana, Francesco; Justo, Alfredo; Ferisin, Giuliano (Phytotaxa, 2022)
Pluteus aesotiensis sp. nov. is described based on several collections from northeast Italy. Phylogenetic analyses of the ITS region place this new species in sect. Celluloderma (/cinereofuscus clade). Morphologically P. aesotiensis is characterized by the combination of a brown, reddish brown to deep yellowish brown pileus, sometimes rugulose at center, globose to broadly ellipsoid spores, fusiform to broadly fusiform pleurocystidia, and clavate caulocystidia present only in the apical part of the stipe. The nrITS phylogenetic analysis supports this taxon as a new species. The description is illustrated with photographs of the basidiomes in habitat and photographs of the main microscopic features.